ESTIMASI KANDUNGAN KLOROFIL TANAMAN KOPI ROBUSTA (Coffea canephora var. Robusta) MENGGUNAKAN NORMALIZED DIFFERENCE VEGETATION INDEX (NDVI) DI BANGELAN, WONOSARI, MALANG - Ajral Mukhlisin; S Soemarno (Jurnal Tanah dan Sumberdaya Lahan, 2020)
Chlorophyll in leaves affects the reflection of infrared light, where healthy plants can reflect more infrared light than unhealthy plants which is one of the factors increasing production in coffee plants. Normalized Difference Vegetation Index (NDVI) is a plant index that utilizes red and infrared light. Therefore, in this study, the algorithm used to determine the chlorophyll content is NDVI. The purpose of this study was to assess the value of chlorophyll content, the value of vegetation index, and to estimate chlorophyll content in coffee plants in PTPN XII Bangelan Village using a remote sensing method. The results showed that the average chlorophyll content of coffee plants assessed using the SPAD (Soil Plant Analysis Development) aid was 65.95 mg g-1. The average Vegetable Index of coffee plants was 0.59. NDVI vegetation index was directly proportional to the value of chlorophyll content in the leaves of coffee plants with the formula of y = 97.665x + 7.684 with R = 0.7153 where the x value is the NDVI value. Thus, remote sensing can be used to estimate the chlorophyll content of coffee plants.